I know that the coefficient $$-\frac{1}{2} \choose k$$ can be simplified by multiplying both the nominator and the denominator by $$2^k$$ and then represented as $$ (-\frac{1}{4})^k {2k\choose k}$$ But what if the upper index is $$\frac{1}{3}$$it seems that our trick do not work anymore, is there anything we can do about it?


There is no nice generalisation from $\binom{-\frac{1}{2}}{k}$ to $\binom{\pm \frac{1}{n}}{k}, 0\leq k \leq n$ available.

We obtain for $n=2$:

\begin{align*} \binom{-\frac{1}{2}}{k}&=\frac{1}{k!} \left(-\frac{1}{2}\right)\left(-\frac{3}{2}\right)\cdots\left(-\frac{1}{2}-(k-1)\right)\\ &=\frac{1}{k!}\frac{(-1)^k}{2^k}(2k-1)!!\\ &=\frac{1}{k!}\frac{(-1)^k}{2^k}\frac{(2k)!}{(2k)!!}\tag{1}\\ &=\frac{(-1)^k}{2^{2k}}\frac{(2k)!}{k!k!}\\ &=\frac{(-1)^k}{2^{2k}}\binom{2k}{k}\\ \end{align*}

and for $n=3$:

\begin{align*} \binom{-\frac{1}{3}}{k}&=\frac{1}{k!} \left(-\frac{1}{3}\right)\left(-\frac{4}{3}\right)\cdots\left(-\frac{1}{3}-(k-1)\right)\\ &=\frac{1}{k!}\frac{(-1)^k}{3^k}(3k-2)!!!\\ &=\frac{1}{k!}\frac{(-1)^k}{3^k}\frac{(3k)!}{(3k)!!!(3k-1)!!!}\tag{2}\\ &=\frac{(-1)^k}{3^{2k}}\frac{(3k)!}{k!k!}\frac{1}{(3k-1)!!!}\\ &=\frac{(-1)^k}{3^{2k}}\binom{3k}{2k}\binom{2k}{k}\frac{1}{(3k-1)!!!}\\ \end{align*}


\begin{align*} (2k)!&=(2k)!!(2k-1)!!\qquad \text{and} \qquad (2k)!!=2^kk!\\ \end{align*}

  • The formula with triple factorials in (2) is somewhat more complicated due to additional factors $(3k-1)!!!$

\begin{align*} (3k)!&=(3k)!!!(3k-1)!!!(3k-2)!!!\qquad \text{and} \qquad (3k)!!!=3^kk!\\ \end{align*}

Note: You might find the generalisation to $\binom{\alpha}{k}$ with $\alpha \in\mathbb{C}, k\geq 0$ used in binomial series or the even more generalized binomial coefficients based upon Gamma functions useful.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.